Stereodynamics in the Collisional Autoionization of Water, Ammonia, and Hydrogen Sulfide with Metastable Rare Gas Atoms: Competition Between Intermolecular Halogen and Hydrogen Bonds. Issue 2 (3rd December 2015) - Falcinelli, Stefano; Bartocci, Alessio; Cavalli, Simonetta; Pirani, Fernando; Vecchiocattivi, Franco
Abstract: Recent experiments on the title subject, performed with a high‐resolution crossed‐beam apparatus, have provided the total ionization cross sections as a function of the collision energy between noble gas atoms, electronically excited in their metastable states (Ng*), and H2 O, H2 S, and NH3 reagents, as well as the emitted electron energy spectra. This paper presents a rationalization of all the experimental findings in a unifying picture to cast light on the basic chemical properties of Ng* under conditions of great relevance both from a fundamental and from an applied point of view. The importance of this investigation is that it isolates the selective role of the intermolecular halogen and hydrogen bonds, to assess their anisotropic effects on the stereodynamics of the promoted ionization reactions, and to model energy transfer and reactivity in systems of applied interest, such as planetary atmospheres, plasmas, lasers, and flames. Abstract : When worlds collide : The investigation of collisional autoionization (CAI) reactions of polar hydrogenated molecules provides unique information on the competitive role of the molecular dynamics of intermolecular hydrogen and halogen bonds. Both interactions control the approach of reactants, but only the second one is strong enough to enhance the reactivity and induce possible molecular orientation effects.